Impact of insurance type on eligibility for advanced heart failure therapies and survival. Issue 8 (11th July 2018) - Hutcheson, Sarah Streeter; Phillips, Victoria; Patzer, Rachel; Smith, Andrew; Vega, J. David; Morris, Alanna A.
Abstract: Background: Medicaid insurance in Georgia provides limited reimbursement for heart transplant (HT) and left ventricular assist devices (LVAD). We examined whether insurance type affects eligibility for and survival after receipt of HT or LVAD. Methods and Results: We retrospectively identified patients evaluated for HT/LVAD from 2012 to 2016. We used multivariable logistic and Cox proportional hazards regression to examine the association of insurance type on treatment eligibility and 1‐year survival. Of 569 patients evaluated, 282 (49.6%) had private, 222 (39.0%) had Medicare, and 65 (11.4%) had Medicaid insurance. Patients with Medicaid were younger, more likely to be Black, with fewer medical comorbidities. In adjusted models, Medicare and Medicaid insurance predicted lower odds of eligibility for HT, but did not affect survival after HT. Among those ineligible for HT, Medicaid patients were less likely to receive destination therapy (DT) LVAD (adj OR 0.08, 95% CI 0.01‐0.66; P  =   .02) and had increased risk of death (adj HR = 2.03, 95% CI 1.13‐3.63; P  = .01). Conclusions: Despite younger age and fewer comorbidities, patients with Medicaid insurance are less likely to receive DT LVAD and have an increased risk of death once deemed ineligible for HT. Medicaid patients in Georgia need improved access to DT LVAD.